Nursing care for cancer patients undergoing anesthesia (Research, Society and Development, 2021)
The objective of this study was to describe the risks associated with anesthesia in cancer patients and nursing care during anesthesia in cancer patients. The research is a bibliographic review of descriptive and qualitative approach. It was carried out in the Databases of Google Acadêmico, BVS (biblioteca virtual em saúde) e SciELO (ScientificElectronic Library Online), with the following research question: what nursing care for cancer patients submitted to anesthesia? Academic articles published between 2012 and 2020 were included, available free of charge. Articles lower than 2012, abstracts, journals that did not contemplate any of the objectives, that did not answer the research question and repeated articles found in the databases mentioned above, which resulted in a final sample of 35 articles, were excluded. Complications general anesthesia in cancer patients are the development of vocal cord paralysis after intubation, prolonged fasting time, pulmonary edema, atelectasis, pneumonia, VAS obstruction (upper airways), bronchospasm, VAS edema, bronchitis and exacerbating COPD (Chronic Obstructive Pulmonary Disease), and the anesthetics used can generate complications such as: weakness of the pharyngeal musculature, respiratory depression, pruritus, nausea ,vomiting, urine retention, decreased gastrointestinal motility, and paralytic bowel obstruction. The role of nurses in anesthetic procedures is fundamental to promote a safe and favorable environment for anesthesia and to perform safe nursing care to have a quiet surgical procedure.